2020
DOI: 10.1002/eji.201948400
|View full text |Cite
|
Sign up to set email alerts
|

TIM‐3 and CEACAM1 do not interact incisand intrans

Abstract: TIM‐3 has been considered as a target in cancer immunotherapy. In T cells, inhibitory as well as activating functions have been ascribed to this molecule. Its role may therefore depend on the state of T cells and on the presence of interaction partners capable to perform functional pairing. Carcinoembryonic antigen‐related cell adhesion molecule (CEACAM1) has been proposed to bind TIM‐3 and to regulate its function. Using a T cell reporter platform we confirmed CEACAM1‐mediated inhibition, but CEACAM1 did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…The Jurkat leukemic T-cell line is a widely used model system for the study of TCR function, 21 and we previously developed a triple parameter TCR signalling reporter cell line (TPR) based on the Jurkat line E6.1. 22 These reporter cells have been proven to be highly suitable to evaluate costimulatory pathways and the function of chimeric antigen receptors, [23][24][25] but to date, their potential to evaluate transgenically expressed TCRs in a high-throughput manner that still reflects physiological T-cell biology as seen in primary human T cells had not been tested. To facilitate highly sensitive and unbiased TCR functional characterisation, we introduced two additional modifications in the TPR cell line.…”
Section: Introductionmentioning
confidence: 99%
“…The Jurkat leukemic T-cell line is a widely used model system for the study of TCR function, 21 and we previously developed a triple parameter TCR signalling reporter cell line (TPR) based on the Jurkat line E6.1. 22 These reporter cells have been proven to be highly suitable to evaluate costimulatory pathways and the function of chimeric antigen receptors, [23][24][25] but to date, their potential to evaluate transgenically expressed TCRs in a high-throughput manner that still reflects physiological T-cell biology as seen in primary human T cells had not been tested. To facilitate highly sensitive and unbiased TCR functional characterisation, we introduced two additional modifications in the TPR cell line.…”
Section: Introductionmentioning
confidence: 99%
“…Further, using various cellular, biochemical and biophysical methods (Gandhi et al, 2018;Haidar et al, 2019;Y.-H. Huang et al, 2016;Sabatos-Peyton et al, 2018;Zhang et al, 2020), we and others have demonstrated a conserved role of the GFCC' faces of hCEACAM1 and hTIM-3 in the heterodimerization between these two proteins (K D of ~ 2-3 μM) (Figure 7-figure supplement 12). Despite these findings, a recent paper (De Sousa Linhares et al, 2020) suggested a lack of appreciable binding of hCEACAM1 by hTIM-3. This is surprising and likely due to a number of factors, including use of incompletely characterized Fc fusion proteins that do not take into account the monomer-dimer equilibrium or structural state of the proteins used or consideration of the relative affinities of the CEACAM1 homodimer (450 nM) and CEACAM-TIM-3 heterodimer (2-3 M).…”
Section: Discussionmentioning
confidence: 94%
“…interactions with its various ligands, a note of caution given the recent studies of others (De Sousa Linhares et al, 2020) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, transplantation and peripheral tolerance was shown to be critically dependent on an undisturbed Tim-3 function [ 43 ]. Whether galectin-9 or CEACAM1 as Tim-3 ligands play essential interactive roles is still discussed controversially [ 44 47 ]. The putative role of Tim-3 for Treg cell function has been characterized by Wang et al .…”
Section: Discussionmentioning
confidence: 99%